Effect of Transcutaneous Auricular Vagus Nerve Stimulation on Protracted Alcohol Withdrawal Symptoms in Male Alcohol-Dependent Patients - Wang, Yong-Mei; Xu, Ya-Yun; Zhai, Yi; Wu, Qian-Qian; Huang, Wen; Liang, Yan; Sun, Yan-Hong; Xu, Lian-Yin (Frontiers in Psychiatry, 2021)
Protracted alcohol withdrawal symptoms (PAWS), characterized by the presence of substance-specific signs and symptoms (including anxiety, irritability, mood instability, insomnia, and cravings), make alcohol abstinence difficult and increase the risk of relapse in recovering alcoholics. The goal of this study was to evaluate the effect of transcutaneous auricular vagus nerve stimulation (taVNS) on PAWS and plasma brain-derived neurotrophic factor (BDNF), interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), and leptin levels in patients with alcohol dependency. A total of 114 patients with alcohol dependence were randomly divided into two groups: the treatment group and the control group. The patients in the treatment group were treated with taVNS of the bilateral auricular concha using an ear vagus nerve stimulator. The Pennsylvania Alcohol Craving Scale was used to evaluate the extent of craving for alcohol. The Self-Rating Anxiety Scale and Self-Rating Depression Scale (SDS) were used to evaluate the extent of anxiety and depression symptoms, respectively. The Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality. Enzyme-linked immunosorbent assay was used to measure plasma BDNF, IL-6, TNF-α, and leptin levels. The results showed that the SDS and PSQI scores were significantly lower in the treatment group than in the control group. Moreover, compared with the control group, the average BDNF levels in the treatment group were significantly increased. These results suggest that taVNS could improve the depression symptoms and sleep quality in alcohol-dependent patients after withdrawal, which might be related to the upregulation of plasma BDNF levels.